MODERN TECHNOLOGY'S ROLE IN ADVANCING SCIENTIFIC LEARNING AND EXPERIMENTATION: INSIGHTS FROM MATHEMATICS AND SCIENCE STUDENTS AT UNIVERSITAS NEGERI MEDAN (UNIMED) - Niken Yolanda; Rahmad Ardiansyah; Wahyu Kurniawan; Muhammad Natsir (International Journal of Teaching and Learning, 2025)
The integration of modern technology into education has profoundly influenced the teaching and learning processes, particularly in mathematics and science. This study explores the role of technological tools in enhancing scientific learning and experimentation among students at Universitas Negeri Medan (UNIMED). A mixed-methods approach was utilized, combining quantitative survey data and qualitative insights to capture a holistic understanding of students’ experiences. The findings reveal that advanced tools such as simulations, virtual laboratories, and data analysis software enhance students’ conceptual understanding, foster engagement, and bridge the gap between theoretical knowledge and practical application. However, challenges persist, including limited access to updated equipment, inadequate training, and technical malfunctions, which disproportionately affect Physics and Chemistry students. To address these issues, the study recommends upgrading laboratory resources, implementing comprehensive training programs, and establishing technical support systems. This research highlights the transformative potential of technology in higher education and provides actionable recommendations to optimize its integration, contributing to the advancement of scientific education in Indonesia.